English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6 answers

First, put in parentheses! I assume you wanted
(-x-6)/(x+6)=-1. What you have written is not the same as this, but it is a very common error to write what you did.
From (-x-6), factor out a common (-1), i.e. a negative sign, to get the top to be (-1)(x+6). Now cancel the x+6 on top and bottom to get -1 left over.

If you did, in fact, mean what you wrote, multiply by x to get
-x^2-6+6x=-x
and then put everything on the right hand side to get
0=x^2-7x+6=(x-1)(x-6),
so x=1 or 6.

2006-10-01 13:14:18 · answer #1 · answered by mathematician 7 · 0 0

Your equation is not clear. You need to use parentheses. The way you have written it, -x -6/x + 6 =-1

first multply the whole eq by -x to get

x^2 +6 -6x = x

Then combine terms

x^2 - 7x + 6 = 0;

This can be solved using the quadratic equation, or it can be factored:

(X - 1)(x - 6), so the solution is x = 1 and x = 6

2006-10-01 13:17:04 · answer #2 · answered by gp4rts 7 · 0 0

Start by multiplying both sides by x

This gives -x^2 - 6 + 6x = -x or

-x^2 +7x -6 = 0

Now you can solve the binomial equation.

2006-10-01 13:10:57 · answer #3 · answered by rscanner 6 · 0 0

Start by multiplying both sides by x:
-x^2-6+6x=-x
-x^2+7x-6=0
x^2-7x+6=0
(x-6)(x-1)=0
x=6,1

2006-10-01 13:14:51 · answer #4 · answered by bruinfan 7 · 0 0

Yes, I can.

-x - 6 / x + 6 = -1

Multiply both sides by " x + 6 "

so... -x - 6 = -x - 6

and add " x " to both sides...

you get 0x - 6 = -6

and add 6 to both sides

you get 0x = 0

This is a problem which has "no solution."
Write that down as your answer.
It is correct.

2006-10-01 13:19:34 · answer #5 · answered by zahbudar 6 · 0 0

can you use brackets plz

2006-10-01 13:12:43 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers